Recursive Descent Parser and Context Free Grammar in Examining Indonesian Sentence Patterns - Meilandri, Ega Citra; Thamrin, Husni (2024 International Conference on Smart Computing, IoT and Machine Learning (SIML), 2024)
Language is the most important supporting tool in communication between humans which aims to convey ideas, thoughts, emotions, feelings or messages to other people. Language can be conveyed orally or in writing. Both forms of language have the same goal, namely to facilitate the delivery of messages clearly and effectively to the recipient of the message. In writing effective sentences, the sentences are built according to correct grammatical rules because they will influence the delivery of the message. Therefore, the author proposes research related to checking sentence patterns which is carried out automatically whether the sentence is in accordance with grammar which has the elements of subject, predicate, object, information (SPOK). The aim of this research is to make it easier to examine sentence patterns. This research uses a recursive descent parser algorithm and context free grammar. The context free grammar algorithm is used to group the types of words and sentence patterns to be examined. Meanwhile, the recursive descent parser algorithm is used to examine Indonesian sentence patterns. The results of this research produced a success rate (%) of 67.2% of the 500 sentences that had been entered.